An Analysis of Students Difficulties in Listening Comprehension at Senior High School - Ulfa Lifia Bahri; Siti Ismahani (FKIP, Universitas Palangka Raya, 2022)
The purpose of this descriptive study was to analyze the difficulties high school students face in listening to the factors that cause these difficulties. Various data collection methods such as questionnaires, interviews, and tests were used in this study and the collected data were analyzed using descriptive statistics, content analysis, and thematic analysis. Research has shown that listening is a difficult skill for students learning a foreign language, and students face a variety of difficulties in listening comprehension, including Lack of vocabulary, lack of concentration, lack of continuity, familiarity with accents, practice, and confidence. The difficulties students face in listening are caused by a variety of factors, including Lack of exposure to language, lack of practice, and lack of confidence. Teachers can address these issues by providing students with vocabulary lists and exercises, familiarizing them with different accents, and encouraging regular listening practice. Group discussion with peers is also a powerful way to improve your students' speaking and listening skills. Overall, this study provides insight into the specific difficulties faced by students and the factors that contribute to those difficulties. This helps teachers create effective strategies and resources for students to improve their listening skills.